2019
DOI: 10.3390/cells8111437
|View full text |Cite
|
Sign up to set email alerts
|

Route of Infection Influences Zika Virus Shedding in a Guinea Pig Model

Abstract: Due to the recent epidemic of Zika virus (ZIKV) infection and resulting sequelae, as well as concerns about both the sexual and vertical transmission of the virus, renewed attention has been paid to the pathogenesis of this unique arbovirus. Numerous small animal models have been used in various ZIKV pathogenicity studies, however, they are often performed using immunodeficient or immunosuppressed animals, which may impact disease progression in a manner not relevant to immunocompetent humans. The use of immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 81 publications
1
11
1
Order By: Relevance
“…ZIKV antigen was also detected in the testes of immunocompetent guinea pigs after subcutaneous and intranasal inoculation [124]. A more recent study demonstrated that immunocompetent guinea pigs are susceptible to ZIKV infection after vaginal inoculation, with viral RNA detected in various tissues including the ovaries and uterus [125]. Infectious virus persisted in vaginal secretions for at least 21 days.…”
Section: Zika Virus: Other Animal Models To Study Sexual Transmissionmentioning
confidence: 93%
See 1 more Smart Citation
“…ZIKV antigen was also detected in the testes of immunocompetent guinea pigs after subcutaneous and intranasal inoculation [124]. A more recent study demonstrated that immunocompetent guinea pigs are susceptible to ZIKV infection after vaginal inoculation, with viral RNA detected in various tissues including the ovaries and uterus [125]. Infectious virus persisted in vaginal secretions for at least 21 days.…”
Section: Zika Virus: Other Animal Models To Study Sexual Transmissionmentioning
confidence: 93%
“…Evidence of ZIKV infection has been detected in the reproductive tracts of several non-murine, non-primate vertebrate species [124][125][126][127]. ZIKV RNA was detected in the testes of tree shrews (Tupaia belangeri) after subcutaneous inoculation [127].…”
Section: Zika Virus: Other Animal Models To Study Sexual Transmissionmentioning
confidence: 99%
“…Similarly, a constant viremia (10 4.4 -10 6.02 RNA copies/ml) was detected from 2 to 5 dpi in Guinea pigs infected via a subcutaneous and vaginal route which peaked at 3 dpi (Saver et al, 2019). Current study viremia initiation is consistent with detection of ZIKV viremia in Rhesus monkeys (Li X. F. et al, 2016), mice (Zhang N. N. et al, 2016), and Guinea pigs (Saver et al, 2019) but the peak of viremia is only comparable with Rhesus monkeys (Li X. F. et al, 2016). ZIKV shedding in urine, salvia, a low load transient viremia was detected at 1-7 dpi and peaked at 3 dpi which is consistent with the detection of viremia in mice (Zhang N. N. et al, 2016) and tree shrews .…”
Section: Discussionmentioning
confidence: 79%
“…A transient viremia (10 6.15 RNA copies/ml) was detected at 1 dpi in immunocompetent mice after SC inoculation (Zhang N. N. et al, 2016). Similarly, a constant viremia (10 4.4 -10 6.02 RNA copies/ml) was detected from 2 to 5 dpi in Guinea pigs infected via a subcutaneous and vaginal route which peaked at 3 dpi (Saver et al, 2019). Current study viremia initiation is consistent with detection of ZIKV viremia in Rhesus monkeys (Li X. F. et al, 2016), mice (Zhang N. N. et al, 2016), and Guinea pigs (Saver et al, 2019) but the peak of viremia is only comparable with Rhesus monkeys (Li X. F. et al, 2016).…”
Section: Discussionmentioning
confidence: 82%
“…Animals models are critical for understanding viral pathogenesis and testing therapeutic interventions. To this end, Saver et al [ 6 ] inoculated guinea pigs by subcutaneous and vaginal routes to mimic the infected mosquito bite and sexual transmission, respectively. By studying multiple tissues with respect to tropism and persistence, they identified sensory and autonomic ganglia in the nervous system as a potential novel niche of ZIKV persistence.…”
mentioning
confidence: 99%